DEIKSIS BAHASA MADURA DALAM PERCAKAPAN MAHASISWA ASRAMA UNIVERSITAS TRUNOJOYO MADURA - Sarmadiyah, Nailir Rahmah (Hasta Wiyata, 2024)
In everyday life, humans cannot be separated from communication activities with others. Humans are social creatures who need to interact with other people. In the communication process the role of language is very necessary. In order for the communication process to run smoothly, a person must understand the relationship between the context and the language spoken. This will be discussed in one branch of linguistics, namely pragmatics. Usually language is packaged and used by prioritizing its efficient function, therefore in pragmatics there is a discussion about deixis. This research will discuss the form of deixis used in Madurese. The research subject is the conversation environment of students at the Trunojoyo Madura University dormitory. The conversation studied was a non-formal conversation style with a relaxed variety. The research method used is descriptive qualitative with conversation data collection techniques using recording equipment and note-taking techniques. From the data obtained, there are five types of deixis that appear in the context of conversations between dormitory students.